FAKTOR-FAKTOR STRATEGIS PENDORONG PENINGKATAN HUBUNGAN KERJASAMA MIGAS RUSIA TERHADAP TIONGKOK TAHUN 2014 - Subhaga, Sri Arya Manik Bagus; Fasisaka, Idin; Widya N, A.A B. Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2016)
ABSTRACT Sino - Russia Gas Deal 2014 is an increase of Russian oil and gas cooperations  with China, which reached 38bcm or equivalent to 400 billion USD. The value of this cooperation agreement is the highest level of transaction in history. An increasing of Russian oil and gas cooperation relationship for China is inseparable from the two crucial momentums ; Ukrainian gas crisis of 2009 and the Russian military intervention to Crimea in 2014. This study aimed to describe the strategic factors that encourage increased cooperation relationship Russian oil and gas to China in 2014. This study used a descriptive qualitative research methods and assessed by using three concept such as energy security : security of demand, Russian oil diplomacy, and geostrategy. Keywords : oil and gas, energy cooperation, energy security, Russia's oil diplomacy.